Implementation of the Community Empowerment Program in Cikeusik District, Pandeglang Regency - Fatulloh Fatulloh; Jaka Permana; Ade Subhan (HK-Publishing, 2025)
This study aims to examine the implementation of the Community Empowerment Program in Cikeusik District, Pandeglang Regency. The implementation indicators include communication, resources, disposition, and bureaucratic structure. The study employs a descriptive-qualitative approach. Key informants include district officials, while other informants comprise the program coordinator, village officials, and three community members. Purposive sampling was used to select community informants. Data collection involved both primary data (gathered through interviews) and secondary data (gathered through observation). Data analysis consisted of four simultaneous activities: data collection, data reduction, data presentation, and conclusion drawing/verification. The study results indicate that the implementation of the Community Empowerment Program in Cikeusik District has not been optimal. Several implementation indicators face challenges, particularly regarding coordination, resources, and community engagement. Program communication has not reached all residents; outreach efforts tend to be limited and unstructured, resulting in many community members lacking a comprehensive understanding of the program. Keywords: Implementation, Empowerment, Community